LIQUIDITY, LEVERAGE, TAX AVOIDANCE: THE MODERATING ROLE OF FIRM SIZE - Rahayu, Sri; Firmansyah, Amrie; Perwira, Hendrik; Saputro, Suryo Kencono Adi (Kesatuan Press, 2022)
This study examines the effect of liquidity and leverage on tax avoidance. In addition, this study employs firm size as a moderating variable. This type of research is quantitative by using purposive sampling. The population in this study are all mining companies listed on the Indonesia Stock Exchange in 2016-2020. Determination of research sample based on purposive sampling method with a total sample of 60 observations. Research data is secondary data accessed through www.idx.co.id and www.idnfinancials.com. This study concludes that liquidity is positively associated with tax avoidance, while leverage is not associated with tax avoidance. Other findings indicate that firm size does not provide a moderating role in testing the effect of liquidity and leverage on tax avoidance. This study suggests that the Indonesia Tax Authority needs to pay attention to the characteristics of certain companies in identifying tax avoidance by companies.